the Effect of LKPD-Assisted Guided Inquiry Learning Model on Students' Understanding of Concepts in Physics Learning - AS, Nurhumairah (PILLAR OF PHYSICS EDUCATION, 2024)
Student learning outcomes in Physics are poor due to several factors. These include poor student understanding of the concepts of the material taught by teachers and  availability of LKPD that does not help students understand the concept. To overcome this, a learning model is needed that actively and directly engages students in the learning process using a guided inquiry model supported by LKPD to improve students' understanding of the concepts. The research employs a Quasi Experimental Design, specifically the Randomized Control Group Only Design. The study population comprises all class XI Phase F students at SMAN 2 Pariaman enrolled in Semester 1 of the 2023/2024 Academic Year. Purposive Sampling is used, with class XI F2 designated as the experimental class and class XI F6 as the control class. Data on students' conceptual understanding are collected through a final test featuring multiple-choice questions. Statistical analyses include normality and homogeneity tests, as well as a two-sample average similarity test. The average conceptual understanding score is 76.29 for the experimental class and 59.54 for the control class. By conducting a similarity test of two averages on students' understanding of concepts at a real level of 0.05 obtained tcount = 5.24 and ttable = 1.99 means tcount > ttable. Thus, the study concludes that the LKPD-assisted guided inquiry learning model significantly enhances students' understanding of concepts in physics learning at SMAN 2 Pariaman.